HUBUNGAN MANAJEMEN WAKTU BELAJAR DAN KOMPETENSI PROFESIONAL PENDIDIK PERSEPSI PESERTA DIDIK DENGAN HASIL BELAJAR KELAS TINGGI - Nabila Ayu; Nelly Astuti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The problem in this research is the learning outcomes of several students in SDN 3 Adipuro that do not meet the completeness standard. The purpose of this study is to identify the correlation between learning time management and the students’ perception of teacher’s professional competence with high class learning outcomes at SDN 3 Adipuro. This type of research was ex post facto corelation. The population was 115 students which 56 students were chosen as the sample. Data collection techniques used were observation, interviews, questionnaires, and documentation studies. Data collection instruments in the form of a questionnaire with a Likert scale has been claimed validity and reliability. Analysis of the data used was Poduct Moment Correlation and Multiple Correlation. The result showed that there was a positive and significant relationship between learning time management and the students’ perception of teacher’s professional competence with high class learning outcomes with a correlation coefficient of 0.534 according to the